TMEM164 is a new determinant of autophagy-dependent ferroptosis. Issue 3 (4th March 2023) - Liu, Jiao; Liu, Yang; Wang, Yuan; Li, Changfeng; Xie, Yangchun; Klionsky, Daniel J.; Kang, Rui; Tang, Daolin
ABSTRACT: Macroautophagy (hereafter "autophagy") is a membrane-mediated biological process that involves engulfing and delivering cytoplasmic components to lysosomes for degradation. In addition to autophagy's pro-survival effect during nutrient starvation, excessive activation of autophagy machinery can also cause regulated cell death, especially iron-dependent ferroptosis. Here, we report a key role of TMEM164 (transmembrane protein 164) in selectively mediating ATG5 (autophagy related 5)-dependent autophagosome formation during ferroptosis, rather than during starvation. In contrast, the membrane protein ATG9A (autophagy-related 9A) is dispensable for the formation of autophagosomes during ferroptosis. TMEM164-mediated autophagy degrades ferritin, GPX4 (glutathione peroxidase 4), and lipid droplets to increase iron accumulation and lipid peroxidation, thereby promoting ferroptotic cell death. Consequently, the loss of TMEM164 limits the anticancer activity of ferroptosis-mediated cytotoxicity in mice. High TMEM164 expression is associated with improved survival and increased immune cell infiltration in patients with pancreatic cancer. These findings establish a new mode of autophagy-dependent ferroptosis.